Sha'rawi's Perception of Economic Solutions for Home Women in QS Al-Ahzab Verse 33 with Tahlili Approach - Annisa Az Zahra; Yeti Dahliana; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The debate between women being allowed to leave the house or stay at home has a long discussion. There are two opposing views on this matter. Looking at the problems discussed, the author uses the tahlili approach method which focuses on the words